Short-term condylar and glenoid fossa changes in infants with Pierre Robin sequence undergoing mandibular distraction osteogenesis. Issue 2 (February 2021) - Susarla, S.M.; Mercan, E.; Evans, K.; Egbert, M.A.; Hopper, R.A.
Abstract: The purpose was to evaluate short-term changes in condylar and glenoid fossa morphology in infants with Pierre Robin sequence (PRS) undergoing early (age <4 months) mandibular distraction osteogenesis (MDO) for the management of severe airway obstruction. Computed tomography data from infants with PRS who had MDO were compared to those of age-matched control infants without facial skeletal dysmorphology. Surface/volume, linear, and angular measurements of the condyle and glenoid fossa were obtained and compared between infants with PRS and controls. Eleven infants with PRS met the inclusion criteria. There were five female and six male subjects with a mean age at the time of MDO of 41 ± 32 days. Prior to MDO, PRS mandibles had a smaller condylar articulating surface area and volume than age-matched control mandibles, with a more laterally positioned condylar axis ( P ≤ 0.05). Following MDO, there were significant increases in condylar articulating surface area and volume, approaching those of normal controls, with further lateral translation of the condylar axis ( P ≤ 0.05). Condyle and glenoid fossa morphology is largely normalized following early MDO in infants with PRS. The condylar axis translates laterally as a result of MDO; this change is not observed with mandibular growth in infants without PRS.